(untitled) (International Journal of Studies in Nursing, 2018)
Background: Shift report is one of the most important factors in patient care to ensure the oncoming nurse can properly care for the patient. Situation, Background, Assessment, and Recommendation (SBAR) is a communication tool that enables the safe transfer of pertinent information to ensure the best quality of care is provided. Communication is one of the key components of bedside nursing practice. Communication ensures that medical errors are avoided, while patient safety and the quality of care are not affected during a patient’s stay. Purpose: The purpose of this study was to compare the risks and benefits of bedside shift report (BSR) versus traditional shift report (TSR). Method: For a proper evidence-based review, the studies were precisely analyzed, and systematically pieced using the top four tiers of evidence hierarchy. Findings: While bedside shift report has been implemented within inpatient settings, it is not always being utilized properly. Upon conclusion of the literature review, evidence supports using bedside shift report to reduce medical errors, safety risks, and improve the quality of care.